2023
DOI: 10.1523/jneurosci.1663-22.2023
|View full text |Cite|
|
Sign up to set email alerts
|

Phase Alignment of Low-Frequency Neural Activity to the Amplitude Envelope of Speech Reflects Evoked Responses to Acoustic Edges, Not Oscillatory Entrainment

Abstract: The amplitude envelope of speech is crucial for accurate comprehension. Considered a key stage in speech processing, the phase of neural activity in the theta-delta bands (1 - 10 Hz) tracks the phase of the speech amplitude envelope during listening. However, the mechanisms underlying this envelope representation have been heavily debated. A dominant model posits that envelope tracking reflects entrainment of endogenous low-frequency oscillations to the speech envelope. Alternatively, envelope tracking reflect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 61 publications
3
10
0
Order By: Relevance
“…Indeed, there is some evidence that auditory cortical entrainment is enhanced for intelligible signals which might explain the larger PLV we see for the syllable train relative to click stimuli ( Xu et al, 2023 ). Moreover, token duration seems to play a less prominent role in the strength of cortical entrainment since tracking is dominated by locking to an acoustic signal's edge landmarks rather than its nucleus, per se ( Oganian and Chang, 2019 ; Oganian et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is some evidence that auditory cortical entrainment is enhanced for intelligible signals which might explain the larger PLV we see for the syllable train relative to click stimuli ( Xu et al, 2023 ). Moreover, token duration seems to play a less prominent role in the strength of cortical entrainment since tracking is dominated by locking to an acoustic signal's edge landmarks rather than its nucleus, per se ( Oganian and Chang, 2019 ; Oganian et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…9 ). LFS were associated with the temporal structure of speech (prosodics and syllabic information) 52 55 , and the lack of performance improvements may be attributed to the stimuli design of single non-word speech tokens, compared to naturalistic stimuli with varying syllabic/prosodic information.…”
Section: Discussionmentioning
confidence: 99%
“…In speech research, early studies reported speech-aligned neural activity on the syllable level (Ahissar et al, 2001;Luo & Poeppel, 2007;Peelle et al, 2013). Although this effect seems to include responses to sharp acoustic onsets (Doelling et al, 2014;Oganian et al, 2023), other research found that neural dynamics can track various structural or 'higher-level' features of speech (for reviews, see Ding & Simon, 2014;Zoefel & VanRullen, 2015a). Later, Ding et al (2016) showed that, only when participants comprehend speech and are therefore able to parse it into various linguistic elements (e.g.…”
Section: Hierarchical Structure (Figure 4)mentioning
confidence: 99%